2019
DOI: 10.1016/j.omto.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Partial Deletion of Glycoprotein B5R Enhances Vaccinia Virus Neutralization Escape while Preserving Oncolytic Function

Abstract: Vaccinia virus (VV) has been utilized in oncolytic virotherapy, but it risks a host antiviral immune response. VV has an extracellular enveloped virus (EEV) form consisting of a normal virion covered with a host-derived outer membrane that enables its spread via circulation while evading host immune mechanisms. However, the immune resistance of EEV is only partial, owing to expression of the surface protein B5R, which has four short consensus repeat (SCR) domains that are targeted by host immune factors. To en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
4
14
0
Order By: Relevance
“…27 It is also reported that partial deletion of the B5R gene increases EEV productivity, which can be applied to improve the efficacy of oncolytic vaccinia viruses. 28 In this study, we confirmed that the IHD-W strain harbors these distinct characteristics compared with other strains (Fig. 1).…”
Section: Discussionsupporting
confidence: 80%
“…27 It is also reported that partial deletion of the B5R gene increases EEV productivity, which can be applied to improve the efficacy of oncolytic vaccinia viruses. 28 In this study, we confirmed that the IHD-W strain harbors these distinct characteristics compared with other strains (Fig. 1).…”
Section: Discussionsupporting
confidence: 80%
“…[86][87][88] For example, introduction of unnatural amino acid residues such as azides on the capsid surface can give access to selective click chemistry. 89,90 Further, genetically modified viruses can enhance TE, 91,92 broaden the tropism, 63,93 enable fluorescent imaging, 85 escape neutralizing antibodies, 94,95 generate stimuli responsive vectors, 96 e.g. by light 97,98 or enzymes, 99 and target cells.…”
Section: Physical Methodsmentioning
confidence: 99%
“…[124][125][126][127] An important application of cfDNA analysis is to guide treatment decisions, especially in targeted therapy. [128][129][130] For example, liquid biopsy to analyze EGFR mutations has been widely used to guide the use of epidermal growth factor receptor-tyrosine kinase inhibitors. 131 Many studies have demonstrated that targeted large-scale parallel sequencing can be used to identify cancer-related driver mutations in the cfDNA of patients with HCC.…”
Section: Next-generation Sequencing and Cfdna Detectionmentioning
confidence: 99%